Personality and attachment to friends - Marušić, Iris (Array, 2011)
Our study examines the relations of attachment and personality dimensions in young adults. Particular focus of the study is attachment to friends, a form of intimate relations that is less frequently represented in attachment research. For this purpose, modified Brennan's Inventory of Experience in Close Relations (Kamenov & Jelić, 2003) and NEO PI-R assessing five personality dimensions (Costa and McCrae, 1992) were administered to the sample of 352 university students. Results demonstrate a variety of relations between two dimensions of attachment to friends and personality traits, both at the domain and facet level. Anxious attachment to friends is primarily related to neuroticism, while avoidance in friendships is mainly characterized by lower results in two interpersonal domains, extraversion and agreeableness.